An Alternate Pragmatism for Going Public - Webber, James (Professor) (Book collections on Project MUSE., 2018)
"A critique of the composition field's engagement with education reform, particularly the practice of "reframing." Reframing is a pragmatic argument establishing or appealing to the professional authority of scholars in an effort to make that professional judgment more persuasive to publics, such as legislators and other policymakers"--Provided by publisher